A Pre-Experimental Study to Assess the Effectiveness of the Structured Teaching Program on Knowledge Regarding Swine Flu Among Adolescents in Selected Government Higher Secondary School at Lucknow - Kannammal, C.; Singh Yadav, Bhoopendra; Pal, Monika; Mishra, Rajni; Danish Rijvi, Mohd (International Journal of Nursing Research, 2023)
Background: The aim has identified that the new influenza A (H1N1) influenza (swine influenza or swine flu) is a respiratory disease of pigs caused by type a influenza virus that regularly causes outbreaks of influenza in pigs. H1N1 virus causes high levels of illness and low death rates in pigs (centers for disease control and prevention. The centers of disease control has identified that influenza viruses from different species infect pigs. The World Health Oranization H1N1 appears to be as contagious as seasonal influenza. India is ranked 3rd among the most affected countries for cases and deaths of swine flu globally. Methods: In this study, the research approach was quantitative research approach quasi-experimental one group pre-test post-test design which was applied. Total 30 samples selected by convenient sampling techniques. The intervention Structured Teaching Program was introduced to the group after the pre-test. Knowledge was assessed by self-structured questionnaire tool before and after the intervention. This study was conducted in selected Government Higher Secondary School At Lucknow. Results: The result revealed that reveals that the pre-test knowledge mean was 7.3 ± 2.07 (SD) which is 36.5% of the total score, whereas in post-test, the mean score (16.1 ± 1.64 [SD]) which is 80.5% of the total score which means that this score reveals that the adolescents under the study had gained knowledge regarding swine flu among adolescents in selected government higher secondary school. Conclusion: The study concluded that the structured teaching program regarding knowledge on swine flu among government higher secondary school students was effective to improve the knowledge among adolescents in selected government higher secondary school.